Implementation of the Local Wisdom-Based Field Trip Video Watching Method as a Means of Developing Early Childhood Education Students - Astuti, Prehaning Yuni; Maulana, Ishaq; Sari, Icha Purnama (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2025)
Indonesia has a variety of tribes, tribes, customs and cultures. Each region has different local wisdom. This local wisdom must be preserved so that all cultures do not fade into the world current. The Playing Group in Pasuruan uses the media to watch field trip videos to introduce local wisdom in their area. The formulation of the problem in this study is:1) What is the procedure for watching the video field trip Vidio Field Trip Based on Local Wisdom as a Means of Student Development (Case Study in the Al-Firdaus Play Group, Tutur District, Pasuruan Regency), 2) How is the implementation of watching the field trip video of the Vidio Field Trip Based on Local Wisdom as a Means of Student Development (Case Study in the Al-Firdaus Play Group, Tutur District, Pasuruan Regency), 3) What is the impact of watching the field trip video of the Vidio Field Trip Based on Local Wisdom as a Means of Student Development (Case Study in the Al-Firdaus Play Group, Tutur District, Pasuruan Regency). The methodology used in this study is qualitative with evaluative analysis. The results of this research are as follows: 1) Preparation which includes: Preparing Equipment, Choosing the Appropriate Video, namely about livestock and its results and processing, 2). Implementation: Organizing the Room, Starting the Video, Teacher Assistance, 3) Closing: Stopping the Video, Cleaning the Equipment, Evaluation and Reflection. he implementation of watching the field trip video went smoothly. All the students were very enthusiastic because they could watch the video on a very large screen, which amazed them. Watching the field trip video is very appropriate and efficient to be carried out for early childhood. The impacts for the students are: expanding knowledge, enhancing imagination and creativity, as well as teaching ethics and discipline.Keywords: Early Childhood, Local Wisdom, Field Trip.